Organisational support for employees with dyslexia: An explorative study in South Africa - Carmen Venter; Lizelle Rossouw (African Journal of Disability)
Background: Dyslexia is a neurodevelopmental disorder that affects reading, writing and spelling. While it is often identified and accommodated in educational settings, employees with dyslexia (EWD) may still face challenges in the workplace as they continue to struggle with this disability throughout their adult lives. While dyslexia can pose challenges for adults in the workplace, accommodations and support measures are available to help mitigate these difficulties.